Application of modified Laffer Curve in the Marriage Market using Exit Costs - Bose, Feler (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Application of modified Laffer Curve in the Marriage Market using Exit Costs The economics literature that deals with the exit costs of marriage has considered primarily the shift from mutual consent divorce to unilateral divorce and has not provided a larger, overall picture of the marriage market under various exit conditions. This paper proposes that a modified Laffer Curve macro model of marriage and divorce provides the best overall picture of the marriage market under various exit scenarios
Keywords: kontrakt; małżeństwo; rozwód; zmodyfikowana krzywa Laffera